2011
DOI: 10.1111/j.1750-3841.2011.02303.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characterization, and Antimicrobial Resistance of Aeromonas Strains from Various Retail Food Products in Mumbai, India

Abstract: A total of 154 food samples (chicken, fish, and ready-to-eat sprouts) from various retail outlets in Mumbai, India, were analyzed for the presence of Aeromonas spp. over a period of 2 y (January 2006 to March 2008). Twenty-two Aeromonas isolates belonging to 7 different species were isolated from 18 (11.7%) food samples. The highest percentages of isolation were from chicken (28.6%) followed by fish (20%) and sprout (2.5%) samples. Aeromonas caviae, A. veronii bv. sobria, and A. salmonicida were the most frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…In the current study, the incidence of A. hydrophila in fish was 3.75%. Our findings showed similarity with the results of Castro-Escarpulli et al (2003) and Nagar et al (2011). The differences from the studies with higher rates may be originated from research seasons, detection methods, sampling procedures and the sanitation applications.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the current study, the incidence of A. hydrophila in fish was 3.75%. Our findings showed similarity with the results of Castro-Escarpulli et al (2003) and Nagar et al (2011). The differences from the studies with higher rates may be originated from research seasons, detection methods, sampling procedures and the sanitation applications.…”
Section: Discussionsupporting
confidence: 76%
“…The incidence of A. hydrophila in fish samples investigated in this study was lower in comparison to those detected in U.S. by Wang & Silva (1999) Nagar et al (2011) stated the presence of A. hydrophila in 3.85% of 52 freshwater fish samples. In the current study, the incidence of A. hydrophila in fish was 3.75%.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…In the previous study, 34 A. hydrophila isolates were collected from diverse locations and it was observed that all of the strains were resistant to ampicillin, carbenicillin, and rifampicin [23]. In addition, 234 isolates of A. hydrophila were tested in an antibiotics assay and it was found more than 90% of isolates were resistant to tetracycline, trimethoprimsulfamethoxazole, and cephalosporins [24]. Furthermore, it was also found that Aeromonas isolates showed resistance to gentamicin, chloramphenicol, ciprofloxacin, and cotrimoxazole [25].…”
Section: Introductionmentioning
confidence: 99%
“…in food fish samples has been well documented in India during the past decades (Vivekanandhan et al, 2005;Yogananth et al, 2009;Nagar et al, 2011). But, few studies have been performed to determine the potential pathogenicity of the isolates, and none to compare the genotypic and phenotypic virulence properties of Aeromonas from food fish samples.…”
Section: Introductionmentioning
confidence: 99%